Case Report: Unveiling the role of genetic abnormalities in myelomatous pleural effusion: a case of IgG lambda-type multiple myeloma - Chen, Shuangyan; Yan, Lanfang; Mo, Yinjuan; Zhou, Daoyin; Chen, Yan (Frontiers in Oncology, 2025)
A 73-year-old male with a history of multiple myeloma presented with progressively worsening left shoulder pain that was unresponsive to conservative management. Following comprehensive diagnostic procedures, including imaging and genetic testing, he was diagnosed with IgG lambda-type multiple myeloma, complicated by the development of myelomatous pleural effusion (MPE). The patient’s treatment regimen consisted of the PDD chemotherapy combination, including Bortezomib, Doxorubicin, and Dexamethasone, alongside adjunctive therapies aimed at controlling the pleural effusion. Post-treatment evaluation revealed resolution of the pleural effusion, with no detectable myeloma cells in the pleural fluid. This case illustrates the clinical utility of combining chemotherapy with supportive treatments for the effective management of MPE in multiple myeloma patients. The patient’s positive response highlights the significance of tailoring therapeutic approaches to the individual, emphasizing the role of personalized care in improving clinical outcomes in similar complex cases of MPE.